2015
DOI: 10.4103/0973-029x.174623
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous architecture of cementodentinal junction in disease: A scanning electron microscopic study

Abstract: Background:The cementodentinal junction (CDJ) forms a biological and structural link between cementum and dentin. This biological link is regarded as a distinct tissue in its own right. Certain important proteins responsible for periodontal regeneration are said to be present in this tissue. Few studies have described the structure and composition of this layer by light and electron microscopy. Scanning electron microscopic studies pertaining to CDJ in health and disease are few and documentation of periodonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The fibril intermingling between the root dentin and cementum was described as point-like processes and occurred only in places at the cement-dentinal interface. No detachment of the cementodentinal junction was reported, unless the specimens were treated by NaOH-maceration method, and it is reported that NaOH-maceration method does not damage collagen fibril structure and architecture [9,13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fibril intermingling between the root dentin and cementum was described as point-like processes and occurred only in places at the cement-dentinal interface. No detachment of the cementodentinal junction was reported, unless the specimens were treated by NaOH-maceration method, and it is reported that NaOH-maceration method does not damage collagen fibril structure and architecture [9,13] .…”
Section: Discussionmentioning
confidence: 99%
“…The average width of the cemento-dentinal junction in the deciduous 2 nd molar may be relatively higher than that of permanent which may be related to the difference between the structure and chemical composition of dentin and cementum between the deciduous and permanent teeth. Also, Sudhakar and Pratebha, 2015 [13] stated that the cement-dentinal junction is rich in unmineralized collagen which gets easily denatured and degraded due to any physiological or pathological changes and any loss of these collagen fibers and other proteins, that may lead to increase in the width of the cement-dentinal junction and its subsequent weakening.…”
Section: Discussionmentioning
confidence: 99%
“…Cementum is composed of two layers of cellular and acellular cementum [ 32 ]. The interface between cementum and dentine is known as the cemento-dentinal junction (CDJ) [ 33 ]. This complex hierarchical structure of the tooth provides a rich source of insights and ideas for the development of new materials via biomimetic research [ 34 ].…”
Section: Demineralisation and Remineralisation Of Teethmentioning
confidence: 99%